PERFORMING RIGHT IN CACHE COPYRIGHT LAW OF INDONESIA - Makkawaru, Zulkifli (Journal of Humanity, 2015)
Performing Right (Performing Rights) in the corpus of laws in Indonesia have not been strong in the rule and the protection of the law. Although the Copyright ACT in recent times revision rule has been loaded but still very narrow so there can take to become a rule of law that can reverse engineer the behavior of society (notably the community of users of copyrighted songs and music) to stick with it.This paper tries to do a review of the literature and the law. The birth of Act No. 28 by 2014 about copyright gives the feel of a broader legal and encouraged to provide protection of economic rights (economic right) over Copyrights in particular Performing Right with an emphasis on fostering recognition of Collective Management Institutions, as well as on Related Rights protection for emphasis that gives economic maximization of existing opportunities of performing actors, producer ponogram, and broadcasters. And thus, created a large corpus of law in the field of Performing Right in Indonesia.